PVT Analysis and Behavioral Modeling of Doherty and Envelope Tracking RF ULP Power Amplifiers using 65 nm CMOS Technology - Muhammad Ovais Akhter; Najam M. Amin; Aurangzeb Rashid Masud (Sir Syed University Research Journal of Engineering and Technology)
This research encompasses both Process-Voltage-Temperature (PVT) considerations and behavioral modeling of two proposed Power Amplifier (PA) designs for wireless communication systems. Process variations, supply voltage changes, and temperature changes provide difficulties for the design and optimization of power amplifiers for wireless communication systems and may have a substantial influence on their effectiveness. PVT analysis and behavioral modeling have been conducted to address the aforementioned challenges and characterize the behavior and performance of the power amplifiers under real-world operating conditions. It investigates the impact of process variations, supply voltage variations, and temperature variations on the performance of the PAs. The insights gained from this analysis contribute to a deeper understanding of the power amplifiers' performance, efficiency, and suitability for specific wireless communication standards, laying the foundation for future advancements in RF power amplifier design. The first design focuses on a Doherty PA (DPA) tailored for low-power short-range applications complying with the IEEE Wireless Personal Area Network (WPAN) standard. The second design explores an Envelope Tracking (ET) supply bias control for low-power long-range applications conforming to the IEEE Wireless Local Area Network (WLAN) standard. By examining these factors, the research ensures that the PAs exhibit reliable and optimal performance under real-world operating conditions. The PVT corners show a change in gain of only 0.4 dB for DPA and 0.9 dB for ET PA. Furthermore, behavioral modeling is employed to characterize the power efficiency of the envelope tracking PA, along with the current efficiency and quotient current on the load current scale. These models provide valuable insights into the behavior and performance of the PAs at a higher level of abstraction. The results and findings contribute to a deeper understanding of the PA’s performance, efficiency, and suitability for specific wireless communication standards, laying the foundation for future advancements in RF power amplifier design.